2004
DOI: 10.1074/jbc.m404426200
|View full text |Cite
|
Sign up to set email alerts
|

Mutual Targeting of Mediator and the TFIIH Kinase Kin28

Abstract: In Saccharomyces cerevisiae, Kin28 is a member of the cyclin-dependent kinase family. Kin28 is a subunit of the basal transcription factor holo-TFIIH and its trimeric sub-complex TFIIK. Kin28 is the primary kinase that phosphorylates the RNA polymerase II (RNA pol II) Cterminal domain (CTD) within a transcription initiation complex. Mediator, a global transcriptional co-activator, dramatically enhances the phosphorylation of the CTD of RNA pol II by holo-TFIIH in vitro. Using purified proteins we have determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 54 publications
2
39
0
Order By: Relevance
“…The general transcription factors used for all of the reactions in this study came from identical aliquots of a single preparation. The kinase assays with purified Mediator complexes, TFIIK, and GST-CTD were performed as previously described (30).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The general transcription factors used for all of the reactions in this study came from identical aliquots of a single preparation. The kinase assays with purified Mediator complexes, TFIIK, and GST-CTD were performed as previously described (30).…”
Section: Methodsmentioning
confidence: 99%
“…We have previously shown that the enhancement of CTD phosphorylation by TFIIH can be completely recapitulated in a reaction containing purified Mediator, TFIIK (the kinase module of TFIIH) and a GST-CTD fusion protein (30). We repeated these assays for the purified wild type, ⌬med19(rox3)-HT, and ⌬med19(rox3)-HMT Mediators.…”
Section: The Middle Module Of Mediator Is Required For Activated and mentioning
confidence: 99%
See 1 more Smart Citation
“…The kinase module has also been shown to negatively regulate transcription, either via Cdk8/Srb10 phosphorylating the pol II CTD prior to formation of the preinitiation complex (PIC) or by its directly phosphorylating DNA-bound activators, thereby leading to their ubiquitin-mediated proteolysis or export from the nucleus (Chi et al 2001). Subsequent to PIC formation, Mediator enhances Kin28 phosphorylation of the pol II CTD at Ser5 (Guidi et al 2004), suggesting a way in which Mediator may positively regulate gene transcription. These and other observations point to a complex role for Mediator as an integrator of intracellular signals.…”
mentioning
confidence: 99%
“…Additionally, yeast Kin28 phosphorylates two subunits of Mediator (i.e., Med4 and Rgr1/Med14), and although the functionally of these modifications is unknown, it has been demonstrated that Mediator significantly enhances the phosphorylation of RNAPII CTD by Kin28 [94,96]. In fact, in vitro assembly of TFIIH into a pre-initiation complex requires Mediator [139], and following transcription initiation, phosphorylation of Ser5 by Kin28 parallels with the release of Mediator from the CTD of RNAPII as promoter clearance occurs [80].…”
Section: Cdk7/cych and Kin28/ccl1-tfb3mentioning
confidence: 99%